2012
DOI: 10.1042/bj20112090
|View full text |Cite
|
Sign up to set email alerts
|

The ligand specificity of the G-protein-coupled receptor GPR34

Abstract: Lyso-PS (lyso-phosphatidylserine) has been shown to activate the G(i/o)-protein-coupled receptor GPR34. Since in vitro and in vivo studies provided controversial results in assigning lyso-PS as the endogenous agonist for GPR34, we investigated the evolutionary conservation of agonist specificity in more detail. Except for some fish GPR34 subtypes, lyso-PS has no or very weak agonistic activity at most vertebrate GPR34 orthologues investigated. Using chimaeras we identified single positions in the second extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 54 publications
0
32
0
Order By: Relevance
“…The combined organic layer was washed with brine, dried over Na 2 SO 4 , and evaporated. The residue was column-chromatographed (hexane/AcOEt = 1:1) to yield acid 13 tert-Butyl O-(tert-Butoxy(diisopropylamino)phosphanyl)-N-(tert-butoxycarbonyl)-L-serinate (17). Bis(diisopropylamino)-tertbutylphoshine (643.1 mg, 2.112 mmol) was dissolved in a mixture of CH 2 Cl 2 (6 mL) and toluene (0.5 mL).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 2 more Smart Citations
“…The combined organic layer was washed with brine, dried over Na 2 SO 4 , and evaporated. The residue was column-chromatographed (hexane/AcOEt = 1:1) to yield acid 13 tert-Butyl O-(tert-Butoxy(diisopropylamino)phosphanyl)-N-(tert-butoxycarbonyl)-L-serinate (17). Bis(diisopropylamino)-tertbutylphoshine (643.1 mg, 2.112 mmol) was dissolved in a mixture of CH 2 Cl 2 (6 mL) and toluene (0.5 mL).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…The residue was column-chromatographed (hexane/ AcOEt = 4:1) to yield 18 (322.7 mg, 0.852 mmol, 90%, colorless oil). 1 13 (19). In order to eliminate traces of water, phosphoamidite 17 (204.1 mg, 0.440 mmol) was dissolved in CH 2 Cl 2 (5 mL) and toluene (0.5 mL), and the solvent was evaporated under vacuum.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…To measure label-free receptor activation, a dynamic mass redistribution (DMR) assay (Corning Epic Biosensor Measurements; Corning Life Sciences, Lowell, MA) with stably transfected human embryonic kidney (HEK) cells (HEK-FlpIn, P2Y 12 in pcDNA5/FRT) was performed as described previously (Schroder et al, 2010;Ritscher et al, 2012). Briefly, cells were seeded into fibronectin-coated Epic 384-well microplates (60,000 cells per well) and exposed to the various compounds.…”
Section: Downloaded Frommentioning
confidence: 99%
“…GPR34 was first described after mining GenBank for novel G protein-coupled receptor (GPCR) sequences and was assigned to the human X chromosome (4). Although lysophosphatidylserine was proposed as a potential endogenous ligand (5), subsequent studies found no support that this is the natural ligand but rather a surrogate agonist (6,7). Hence, GPR34 is still classified as an orphan in the International Union of Basic and Clinical Pharmacology database (8).…”
mentioning
confidence: 99%